Analysis of Sale and Purchase Agreement Underhand for the Transfer of Home Ownership Loans - Taufika Hidayati; Zetria Erma (LEGAL BRIEF, 2023)
The need for home ownership for the community has become a very important need at this time. The government in collaboration with banks provides convenience facilities to the public as debtors through Housing Loans (KPR) which have monthly installments determined by the Bank as a creditor in accordance with the ability of the debtor. During the mortgage process, the creditor and debtor enter into a credit agreement. In the Mortgage Act number 4 of 1996 it is regulated regarding agreements between the Debtor as the mortgagee and a financial institution, in this case the Bank as the mortgagee that as long as the installments have not been paid off, the certificate of land rights is still in the bank as collateral bound by agreement Deed of Encumbrance of Mortgage made before the PPAT as an authorized official. Using normative juridical research that occurs in people's lives, this article discusses buying and selling land that is still under credit guarantee as the basis for the transfer of rights through private agreements that are not made before the PPAT and how the legal force of ownership of land rights is for the seller who buys the land. . In the results of this study it can be concluded that the credit agreement between the bank as the creditor and the debtor only binds the parties contained in the agreement and the transfer of house loans must be made before the PPAT with the knowledge of the bank as the creditor if the debtor wants to sell or does not want to continue credit again